Digital Communication Strategies for Enhancing Corporate Sustainability: A Strategic Framework for Digital Business Transformation - Hayati, Setiyo; Setiawati, Isti Budhi; Novrianto, L.M. (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
Corporate sustainability has become a strategic priority for organizations operating in an increasingly digitalized business environment. Alongside this shift, digital communication has evolved into a critical managerial function that enables corporations to communicate sustainability values, enhance transparency, and engage diverse stakeholders. This study aims to examine how digital communication strategies contribute to enhancing corporate sustainability within the context of digital business transformation. Employing a qualitative research design with a library research approach, this study synthesizes relevant literature from peer-reviewed journals, academic books, and reputable institutional reports related to digital communication, sustainability, ESG, and digital business strategy. The collected data were analyzed thematically to identify key strategic dimensions linking digital communication with sustainable corporate practices. The findings reveal five main pillars of effective digital communication strategies for corporate sustainability: digital transparency and sustainability disclosure, stakeholder engagement through digital platforms, strategic alignment between sustainability and digital business objectives, data-driven and AI-enabled sustainability communication, and corporate reputation building as a source of competitive advantage. These dimensions demonstrate that digital communication functions not merely as a supportive tool, but as a strategic enabler of sustainable value creation. This study contributes to the literature by offering an integrated strategic framework that connects digital communication with corporate sustainability and digital transformation. Practically, the findings provide insights for corporate leaders and communication professionals in designing sustainability-oriented digital communication strategies that support long-term business resilience.